Isolation and structural elucidation of two new labdane diterpenoids from the aerial part of Roylea cinerea. (September 2015) - Sharma, Reena; Chebolu, Rajesh; Ravikumar, P.C.
Graphical abstract: Highlights: Two new diterpenoids, cinereanoid A and B were isolated from Roylea cinerea . The structures were determined by using IR, MS, 1D and 2D NMR techniques. The structure of compounds1, 2 and3 were confirmed by X-ray crystallography. Abstract: Two new labdane diterpenoids, cinereanoid A (1 ) and cinereanoid B (2 ), along with five known compounds, calyone (3 ), pilloin (4 ), 1-methylindole-3-carboxaldehyde (5 ), β-sitosterol (6 ) and stigmasterol (7 ) were isolated from the aerial parts of Roylea cinerea (Lamiaceae). The new structures were determined by using IR, MS, 1D, 2D NMR spectroscopy. The structure of both new compounds was further confirmed by single crystal X-ray crystallographic analysis. In this study we have also reported single crystal X-ray structure of compound3 which unambiguously confirmed the relative stereochemistry of tertiary hydroxyl and methyl groups, as it was not established by earlier report. Compounds4 and5 were isolated for the first time from this plant. In view of very few reports about this species, this report has increased the phytochemical knowledge about R. cinerea .